Germination performance of Syagrus romanzoffiana seeds subjected to water and salt stress - de Souza, Antonio Maricélio Borges; Campos, Thiago Souza [UNESP]; Vieira, Guilherme Rodrigues [UNESP]; da Silveira, Mariana Martins [UNESP]; Braga, André Caturelli [UNESP]; Patricio, Murilo Paes [UNESP]; Mazzini-Guedes, Renata Bachin; Ferraz, Marcos Vieira; Pivetta, Kathia Fernandes Lopes [UNESP] (Universidade Estadual de Londrina, 2024)
Queen palm (Syagrus romanzoffiana) reproduces through seeds, which typically germinate slowly and unevenly. These seeds face various abiotic stresses, including water and salt stress, which hinder water uptake and germination. This study aimed to assess the germination of queen palm seeds under water and salt stress conditions. We employed a completely randomized experimental design with four replications, using a factorial arrangement (2 × 5) involving two osmoconditioning agents (NaCl and PEG 6000) and five osmotic potentials (0.0 - control, -0.3, -0.6, -0.9, and -1.2 MPa). Key outcomes measured were germination percentage, germination speed index, and mean germination time. Results showed that NaCl significantly affected germination percentage, which decreased with lowering osmotic potential. Significant declines in seed germination were observed starting from -0.6 MPa. Both germination speed index and mean germination time were adversely affected by the osmotic potentials, regardless of the osmoconditioning agent used. Under water stress induced by PEG 6000, seeds germinated later and over an extended period compared to those under NaCl stress. The study concluded that queen palm seeds exhibit tolerance to both water and salt stress, managing to germinate even at the lowest tested osmotic potential (-1.2 MPa).
Desempenho germinativo de sementes de Syagrus romanzoffiana submetidas aos estresses hídrico e salino
Keywords: Abiotic stress; Arecaceae; NaCl; Osmotic potential; PEG 6000; Stress tolerance